Supporting parents of children with learning disorders: a systematic review of intervention strategies - Guerra, Giulia Carlotta; Positano, Maria Teresa; Sperati, Alessandra; Passaquindici, Ilenia; Logrieco, Maria Grazia; Lionetti, Francesca; Spinelli, Maria; Fasolo, Mirco (Frontiers in Psychology, 2025)
IntroductionSpecific Learning Disorder (SLD) is a neurodevelopmental condition affecting 5–15% of children worldwide, typically involving difficulties in reading, writing, and/or mathematics. Dyslexia is the most common subtype. These disorders impact both children and their parents, highlighting the need for emotional and educational support to help families manage SLD-related challenges. Although various parenting programmes exist, little is known about which features make some interventions more effective than others.MethodsThis systematic review assessed the effectiveness of psychotherapeutic and psychoeducational parenting interventions. A comprehensive search was conducted across multiple databases for studies published between 1950 and 2024, following PRISMA guidelines. From 1,519 records, 10 studies met the predefined inclusion criteria.ResultsThe included studies showed that parental support interventions improved parents’ emotional well-being and coping strategies. These improvements were linked to better academic, behavioural, and social outcomes in children. Interventions differed in format and delivery, but all focused on strengthening parental skills and knowledge.DiscussionParenting interventions that combine emotional and educational support appear beneficial for both parents and children. They foster environments that support children’s development. Further research is needed to identify the most effective components and delivery methods across diverse populations.